Aktivitas Penggunaan Portal TELKOM sebagai Media Komunikasi Internal terhadap Pemenuhan Kebutuhan Informasi Karyawan PT. TELKOM DCS REGIONAL SEMARANG - Sasongko, Annisa Febiastu (Jurnal The Messenger, 2017)
The major functions of Telkom Portal as an electronic communication tool are to providing and serving information through a virtual format technology system for the employees. The study attempts to identify the relationship between employee activities of using Telkom Portal as an internal communication medium to the fulfillment of corporate information needs and interest. It also assesses employee social cognitive elements and social interaction at the work place. The results shows that Telkom portal usage activity as internal media is included in high category (51.30%) which means more than half of respondents utilize Telkom portal as information source to fulfill information requirement of company either in center or branch office. While the level of fulfillment of employee information needs is also included in the high category with the percentage of 55.13% indicating accessing Telkom portal can meet the information needs. And the influence of interaction in the work environment is in the high category (66.67%) proves that through social interaction the employees can increase the level of fulfillment of information needs of the company.